Potential of palm oil for biodiesel production. Issue 11 (2nd November 2017) - Sakulsuraekkapong, Jittipun; Pairintra, Rattanachai; Thepa, Sirichai
ABSTRACT: This paper studies the potential of palm oil for producing biodiesel. In the analytical procedures, the demand of diesel in a country is reviewed and illustrated based on a set of previous data dating back 17 years from 1993 to 2009. The reviewed data are then compared with the demands of palm oil, B5, B100, and with GDP in a country. The forecasting process is performed through 15 years by setting a mathematical model using the linear regression analysis. Then, the survey of the quantity of palm oil in each region of Thailand was carried out. The potential studies in terms of economics are estimated by setting possible assumptions. The potential of palm oil which used to produce biodiesel in different classes based on the assumption of crude palm oil (CPO)-blending product price at 15 Baht/liter. The studied price of B100 is 26.88 Baht/liter, B2 is 29.93 Baht/liter, B5 is 29.83 Baht/liter and B10 is 29.18 Baht/liter respectively. Any proportion of biodiesel, known as B5 and B10, price of about 29.83 and 29.18 are calculated, respectively. The results of this study show that the potential of biodiesel production by palm oil in Thailand is extremely positive. However, the extracted price of palm oil is higher than that of the final competing product, petroleum diesel.